Optimization Manufacturing System Model with Recycling Oriented - Hasibuan, Abdurrozzaq; Ekalestari, Susi; Rahman Suleman, Abdul; Khadijatul Z Harahap, Adek; Hasibuan, Masnilam; Simarmata, Janner; Novita, Desi; Sumartono, Eko; Daengs GS, Achmad; Saputra, Syifa; Intan Purba, Mas; Hidayat, Khoirul (International Journal of Engineering and Technology, 2018)
To reuse of used or damaged products is known as recycle. Recycling will reduce the exploitation of natural resources and the accumulation of waste in the environment. This research shows that there is an opposite relationship between profits and recycling level. The higher the profit obtained, the lower the recycling rate achieved. On the contrary, the higher the level of recycling achieved, the lower the profits earned. The result of this research also shows that the collection of efficient recycling level planning for the system is within the target range of a certain value. To get better understanding of the characteristics of the system, additional research is needed on the extreme conditions of the system. First, a condition that describes that the system is only oriented towards recycling (internally and externally), and secondly, profit-oriented (does not recycle at all).Â